Early recurrent neonatal tongue glial heterotopia presenting with acute airway obstruction: the first case report - Zhao, Junwei; Wang, Xiangrong; Yin, Fan; Chu, Jing (Frontiers in Pediatrics, 2026)
BackgroundGlial heterotopia is a rare congenital developmental anomaly characterized by the presence of mature glial tissue outside the central nervous system. It most commonly affects the nasal region, while tongue involvement, particularly at the base of the tongue, is extremely uncommon.CaseThis case represented the first reported instance of early postoperative recurrence of tongue glial heterotopia. We described a 24-day-old male infant diagnosed with tongue glial heterotopia complicated by pneumonia and presenting with airway obstruction. The patient initially underwent conservative local excision of the lesion; however, the lesion rapidly recurred within three weeks postoperatively. A second, more extensive surgical resection with a 5-mm safety margin was subsequently performed. Histopathological examination of both specimens confirmed the diagnosis of glial heterotopia.ConclusionThis report provided a systematic overview of the diagnostic and therapeutic process, including a one-year postoperative follow-up, during which no recurrence or complications were observed. The clinical course of this case highlighted the potential for early recurrence of tongue glial heterotopia following incompletely conservative excision (with the incision placed along the tumor margin). Our findings suggest that early surgical intervention stabilizes neonates with dyspnea and secures a patent airway. Moreover, extensive resection—defined as extending the incision approximately 5 mm into normal tissue—is essential in tongue glial heterotopia to achieve complete pathological clearance and minimize the risk of recurrence.